1999
DOI: 10.1074/jbc.274.22.15401
|View full text |Cite
|
Sign up to set email alerts
|

The A1 and A2 Subunits of Factor VIIIa Synergistically Stimulate Factor IXa Catalytic Activity

Abstract: Factor VIIIa, the protein cofactor for factor IXa, is comprised of A1, A2, and A3-C1-C2 subunits. Recently, we showed that isolated A2 subunit enhanced the k cat for factor IXa-catalyzed activation of factor X by ϳ100-fold (ϳ1 min ؊1 ), whereas isolated A1 or A3-C1-C2 subunits showed no effect on this rate (Fay, P. J., and Koshibu, K. J. (1998) J. Biol. Chem. 273, 19049 -19054). However, A1 subunit increased the A2-dependent stimulation by ϳ10-fold. The K m for factor X in the presence of A2 subunit was unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…11 for a review). Recent studies have shown that modulation of factor IXa by the isolated A2 subunit enhances the k cat for factor Xa activation by ϳ100-fold (12) and that the isolated A1 subunit synergizes this effect (13). This A1-dependent increase in A2 cofactor activity (Ͼ15-fold) did not result from direct interaction with factor IXa but rather altered the interaction of A2 subunit with the protease.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…11 for a review). Recent studies have shown that modulation of factor IXa by the isolated A2 subunit enhances the k cat for factor Xa activation by ϳ100-fold (12) and that the isolated A1 subunit synergizes this effect (13). This A1-dependent increase in A2 cofactor activity (Ͼ15-fold) did not result from direct interaction with factor IXa but rather altered the interaction of A2 subunit with the protease.…”
mentioning
confidence: 97%
“…lier studies, the isolated A1 and A2 subunits of factor VIIIa were prepared following proteolysis of recombinant factor VIII by thrombin (12,13). However, subsequent subunit purification yielded relatively low levels of A2 subunit due to continued association with the A1/A3-C1-C2 dimer.…”
Section: Isolation and Purification Of Factor Viiia Subunits-in Ear-mentioning
confidence: 99%
“…Because this Asn is contained within the N-X-(T/S) N-linked glycosylation site consensus sequence (31), failure to identify this residue provides direct support for utilization of Asn 41 for N-linked glycosylation. Stimulation of A2 by A1 Forms-We previously demonstrated that the isolated A2 subunit possesses limited cofactor activity in stimulating factor IXa-catalyzed activation of factor X (14), and this activity is markedly enhanced in the presence of A1 subunit (15,16). To gain insights into critical regions of A1 required for this stimulation of A2, the cofactor activity of A2 in the presence of the native form and the two truncated A1 forms were compared using a factor Xa generation assay.…”
Section: A1 and A1mentioning
confidence: 99%
“…Interactive sites for factor IXa are localized to A2 and A3 domains (11)(12)(13). Recent studies have shown that modulation of factor IXa by the isolated A2 subunit enhances the k cat for factor Xa activation by ϳ100-fold (14) and that the isolated A1 subunit synergizes this effect (Ͼ15-fold) to alter the interaction of A2 subunit with the protease (15,16).…”
mentioning
confidence: 99%
“…In contrast, the factor VIIIa A2 domain directly modulates the catalytic activity of factor IXa, which is further enhanced by the A1 domain, markedly increasing the k cat for factor X activation. 14,15 Although the isolated A2 domain binds with low affinity to factor IXa, it contributes significantly to protease-cofactor affinity in the membrane-bound enzyme complex. 16 Thus, the factor IXa-A2 domain interaction appears to be the critical protein-protein interface for cofactor enhancement of factor X activation.…”
Section: Introductionmentioning
confidence: 99%